A strengthened solution to option manipulation. Issue 3 (25th July 2022) - Aslam, Bilal; Zhang, Changyong
Abstract: Thanks to the reduced price and less exposition to sudden crashes or price hikes, the Asian option is among the most favorable hedging instruments that are hard to be manipulated, in both the commodity market and executive compensation plan. Since the creation of the option, the main focus has been more on how to price it accurately while much less on how to explore deeper the benefits that the option offers. In this paper, a new type of path-dependent option, referred to as the average-Asian option, is introduced to reduce further the volatility of the underlying price risk and minimize option manipulation threat. The price is proved to be less than that of the standard option. It is additionally shown by numerical results that, when granted at the money, the proposed option is on average about 49.32% and 5.45% cheaper than the standard and Asian options, respectively. Furthermore, the option is less sensitive than the Asian counterpart, at both the front-end and the back-end price manipulation.